5G Technology Deployment: A Thorough Examination of the Potential and Difficulties for Environmental Sustainability, Human Health, and Sociotechnical Systems - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2026)
The introduction of 5G technology presents challenges in the areas of human health, environmental sustainability, and socio-technical systems, but it also holds the promise of revolutionary improvements in healthcare, industry, and connectivity. The purpose of this study is to assess the effects of 5G, pinpoint areas in need of further research, and suggest ways to minimize its negative effects while optimizing its positive ones. Statistical analysis, qualitative reviews, and quantitative simulations were all incorporated into a mixed-methods approach. Mathematical models simulated the impacts of 5 G on health (e.g., obesity risk), the environment (e.g., carbon emissions), and sociotechnical systems (e.g., the digital divide) from 2020 to 2025, using data from various sources. 5G lowers industrial downtime by 25% and improves healthcare outcomes by 20% through remote surgeries. However, it increases the risk of obesity by 30%, carbon emissions by 35.5%, and the digital divide by 137.9%. These effects are successfully balanced by mitigation techniques like screen time limits, the use of renewable energy, and rural 5G projects. 5G's benefits can be maximized through sustainable and equitable. To guarantee long-term societal benefits, its difficulties must be proactively mitigated. Adopt renewable energy for 5G infrastructure, launch public health campaigns, and form alliances to close the digital divide while continuing research trials on the long-term effects.